1999
DOI: 10.18174/njas.v47i2.471
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen and the method of application on yield and quality of broccoli

Abstract: The effects of the rate and the method of N application on yield and quality of broccoli cv. Emperor were studied during 3 seasons at Andijk and Lelystad, Netherlands. Different amounts of N fertilizer were applied broadcast or band placed at planting. Band placement of fertilizer increased the yield in 5 out of 8 experiments. Application of N resulted in larger heads. No relationship was found between soil mineral N at planting and optimum N application because of the narrow range of soil mineral N at plantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…The early-broccoli system had fresh yields of 22.2 and 22.9 Mg ha and late-broccoli yielded 25.0 and 36.2 Mg ha , in 2009 and 2010, respectively. Similar yields, 16 to 35 Mg ha , have been reported in the literature [2,[6][7][8][9]. The lower yield in the early-broccoli compared to the late-broccoli system agrees with previous research, which also found lower total and head plant mass in summer harvested broccoli compared to autumn harvest [39], likely due to different environmental conditions during the broccoli growth periods.…”
Section: Broccoli Harvestsupporting
confidence: 89%
See 1 more Smart Citation
“…The early-broccoli system had fresh yields of 22.2 and 22.9 Mg ha and late-broccoli yielded 25.0 and 36.2 Mg ha , in 2009 and 2010, respectively. Similar yields, 16 to 35 Mg ha , have been reported in the literature [2,[6][7][8][9]. The lower yield in the early-broccoli compared to the late-broccoli system agrees with previous research, which also found lower total and head plant mass in summer harvested broccoli compared to autumn harvest [39], likely due to different environmental conditions during the broccoli growth periods.…”
Section: Broccoli Harvestsupporting
confidence: 89%
“…Cole crop (Brassica vegetables), in particular, produce optimal yields with high N applications, ranging from 270 to 550 kg N ha for broccoli (Brassica olecerea var italica L.) [4,[6][7][8][9]. Cole crop 1 in the field at harvest [2,3], and post-harvest mineral N losses are more related to crop residue N rather than N fertilizer remaining in the soil [3].…”
Section: Introductionmentioning
confidence: 99%
“…The improved yield parameters associated with higher N rates are supported by the higher percentage of N accumulation in leaf tissue (Table 4). Nitrogen accumulation in the aboveground portion of the plant increases with increasing rate of N fertilizer (Everaarts and De Willigen, 1999;Zebarth et al, 1995). In a study by Kowalenko and Hall (1987), high N rates significantly increased N in the leaf tissue and broccoli head without stimulation of the vegetative growth.…”
Section: Resultsmentioning
confidence: 98%
“…Brassica oleracea (broccoli), in the Brassicaceae, is a vegetable crop that requires great amounts of nitrogen fertilizer. To obtain a high yield, 270–465 kg ha −1 of nitrogen is needed (Everaarts and Willigen 1999; Feller and Fink 2005). Like other non‐leguminous plants, broccoli does not have a natural association with root‐nodulating bacteria such as Rhizobium .…”
Section: Introductionmentioning
confidence: 99%